The Role of Islamic Finance in Promoting Economic Justice and Financial Inclusion among Marginalised Communities - Abubakar Muhammad, Adamu; Ibrahim, Aliyu; Yakub, Abubakar Aliyu; Khan, Huma; Hamzah, Namungo (Universitas Muhammadiyah Surakarta, 2025)
The unique framework provided by Islamic banking and finance, which is based on social welfare, equity, and moral principles that forbid exploitative practices like interest (riba), makes it particularly pertinent to underprivileged groups that experience structural economic marginalization. Because of structural obstacles and a lack of trust, many vulnerable groups continue to be neglected by traditional financial institutions, even in spite of the expansion of financial inclusion initiatives. The purpose of this study is to investigate the ways in which Islamic financial instruments, including qard al-hasan (benevolent loans), zakat (almsgiving), waqf (endowment), and profit-and-loss sharing models like mudarabah and musharakah, can be used to advance economic justice and increase financial inclusion in these communities. Purposive sampling, case study analysis, content analysis, and documentary/secondary data are all used in this qualitative study to examine how Islamic Financial Institutions (IFIs) contribute to inclusive growth. Thematic analysis is employed to find trends and evaluate the success of Islamic finance projects relative to traditional financial methods. According to preliminary research, Islamic finance's ethical investment practices, wealth redistribution, and risk-sharing all greatly enhance social justice and economic empowerment. Conclusion: The study comes to the conclusion that incorporating Islamic finance into national financial inclusion plans can be a long-term solution to combat poverty and promote equitable growth. It also makes policy suggestions to fortify its institutional and legal foundation. Economic justice and financial inclusion for underserved populations can be greatly improved by incorporating Islamic banking concepts into national financial systems.